Estimasi Land Subsidence Dengan Metode Differential Interferometry Synthetic Aperture Radar (Dinsar) Di Pantura Kota Semarang - Alfita Ilfiyaningrum; Rini Kusumawardani; Fisa Savanti; Bambang Setyohadi Kuswarna Putra; Nur Aida (Fakultas Teknik Universitas Pasir Pengaraian, 2023)
Land subsidence is a natural phenomenon that occurs due to changes in the position of an object in the vertical direction. There are several factors that cause this phenomenon, including excessive use of ground water, heavy surface loads, and changes in land cover that are not in accordance with the carrying capacity and carrying capacity of the soil. Considering the importance of this phenomenon to human life in general, and infrastructure in particular, regular monitoring must be carried out to determine the magnitude of land subsidence. Monitoring the occurrence of land subsidence can be done using the DINSAR method. This method uses phase differences in remote sensing images from the Sentinel 1 satellite to determine changes in the height of a location from two image data collection times. Data processing with GIS support can be carried out to obtain differences in displacement or movement of the ground surface during the two data collection times. Measuring land subsidence value in the Pantura area uses image data from January 2022 to January 2023. From this research, the maximum value of land subsidence is 2.5 cm in 1 month, 5 cm in 3 months, and 7.5 cm in 1 year. The linear function of land subsidence [y] according the data is y = 4.8058t + 2.8641, where t is the time parameter. With this function, the estimated land subsidence of Pantura Kota Semarang in two years is 12.48 cm.